THE FIRST TWELVE MAQOM SYSTEM OF SHASHMAQOM AND ITS COMPONENTS - Khamrokulov Naimdjon Bakhronovich (American Journals Publishing, 2025)
This article explores the structural, modal, rhythmic, and historical foundations of the first twelve maqoms that form the classical Shashmaqom system. As one of the most influential musical heritages of Central Asia, Shashmaqom embodies centuries of cultural experience reflected in its melodic, rhythmic, and poetic dimensions. The study examines the organizing principles of the maqom cycles, their modal characteristics, compositional layers, performance traditions, and internal structural components such as nasr, tasnif, ufar, savt, and tarona. By analyzing these elements, the article highlights the unique complexity of Shashmaqom’s first twelve maqoms and their significance in preserving artistic identity in the region’s musical culture.
Keywords: Shashmaqom, maqom system, modal structure, traditional music, Central Asian heritage, rhythm cycles, classical repertoire.